2019
DOI: 10.1101/730838
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic time-locking mechanism in the cortical representation of spoken words

Abstract: Computational modeling of cortical responses to spoken words highlights the relevance of temporal tracking of spectrotemporal features, which is likely pivotal for transforming the acoustic-phonetic features into linguistic representations. AbstractHuman speech has a unique capacity to carry and communicate rich meanings. However, it is not known how the highly dynamic and variable perceptual signal is mapped to existing linguistic and semantic representations. In this novel approach, we utilized the natural a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…In line with this interpretation, the magnitude of phase locking of auditory cortical responses to on‐going speech has been demonstrated to decrease with diminishing speech intelligibility (Peelle et al, 2013). Our present non‐invasive recordings are in line also with related electrocorticographic findings (Chang et al, 2010; Mesgarani & Chang, 2012; Zion Golumbic et al, 2013) and extend them by suggesting specific processing of speech sounds among other natural sounds, not only during early acoustic encoding (Nora et al, 2020) but also during real‐life‐like auditory processing, presumably via accentuated top‐down modulatory activity suggested by the current results.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In line with this interpretation, the magnitude of phase locking of auditory cortical responses to on‐going speech has been demonstrated to decrease with diminishing speech intelligibility (Peelle et al, 2013). Our present non‐invasive recordings are in line also with related electrocorticographic findings (Chang et al, 2010; Mesgarani & Chang, 2012; Zion Golumbic et al, 2013) and extend them by suggesting specific processing of speech sounds among other natural sounds, not only during early acoustic encoding (Nora et al, 2020) but also during real‐life‐like auditory processing, presumably via accentuated top‐down modulatory activity suggested by the current results.…”
Section: Discussionsupporting
confidence: 91%
“…We have recently shown that MEG responses to speech sounds reflect the sounds' spectrotemporal characteristics in a time‐locked manner, whereas similar time locking is not observed for environmental sounds or human non‐speech sounds with comparable spectrotemporal modulations (Nora et al, 2020). The results speak for neural activation specifically tracking the speech sound spectrogram, possibly essential for encoding relevant acoustic–phonetic features during speech processing.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations